Behavioral Circadian Timing System Disruptors and Incident Type 2 Diabetes in a Nonshift Working Multiethnic Population. (21st May 2020) - Muilwijk, Mirthe; Stenvers, Dirk Jan; Nicolaou, Mary; Kalsbeek, Andries; van Valkengoed, Irene G.M.
Abstract : Objective: This study aimed to describe distributions of behavioral circadian disruptors in a free‐living setting among a nonshift working multiethnic population, estimate the associated risk of type 2 diabetes (T2D), and determine whether disruptors account for ethnic differences in T2D. Methods: Participants from six ethnic groups were included (Amsterdam, the Netherlands; n = 1, 347‐3, 077 per group). Multinomial logistic regression was used to estimate ethnic differences in disruptors, such as skipping breakfast, eating erratically, and sleep duration. Associations between disruptors and incident T2D and the interaction by ethnicity were studied by Cox regression. Results: Ethnic minority populations skipped breakfast more often, timed meals differently, had longer periods of fasting, ate more erratically, and had more short/long sleep durations than the Dutch. Night snacking from 4 am to 6 am (HR: 5.82; 95% CI: 1.42‐23.91) and both short (HR: 1.48; 95% CI: 1.03‐2.12) and long sleep (HR: 3.09; 95% CI: 1.54‐6.22), but no other disruptors, were associated with T2D. The higher T2D risk among ethnic minority populations compared with Dutch did not decrease after adjustment for last snack or length of sleep. Conclusions: Although prevalence of circadian disruptors was higher among ethnic minority populations and some disruptors were associated with T2D, disruptors did not account for ethnic differences in T2D risk.